Obtainment of the Immunomagnetic Particles for Francisella tularensis Cells Detection - S. S. Vetchinin; P. Kh. Kopylov; N. V. Kiseleva; O. G. Nikolaeva; A. V. Gavryushkin (Проблемы особо опасных инфекций, 2011)
Obtained are the immunomagnetic particles with the immobilized highly-specific monoclonal antibodies FB 11-x to Francisella tularensis. Their usage in enzyme-linked immunoassays made it possible to detect 105 - 106 CFU/ml of F. tularensis. The binding of the bacterial cells with IMP was confirmed by the results of fluorescent microscopy.